Efektivitas Alat Permainan Edukatif (APE) terhadap Perkembangan Kognitif Anak Usia Dini - Peby Dwi Damayanti; Heri Yusuf Muslihin; Taopik Rahman (AS-SABIQUN, 2022)
The purpose of writing this article is to find out whether educational game tools are effective for early childhood cognitive development. This research is library research, namely research that uses library data collection methods, or research whose objects are extracted from various library information (books, encyclopedias, scientific journals, and documents). The effectiveness of the Educational Game Tool (APE) is quite effective on Early Childhood Cognitive Development. There are several educational game tools, both modern and traditional that are useful for improving children's cognitive development, including 1) Role playing, 2) Congklak, 3) Playing Legos, 4) Puzzles. It can be said that through some educational game tools it is effective to improve children's cognitive development such as puzzle games, congklak, and so on, while some educational games are not effective to improve early childhood cognitive development.